2007
DOI: 10.1117/12.740148
|View full text |Cite
|
Sign up to set email alerts
|

<title>MHT tracking for crossing sonar targets</title>

Abstract: Sometimes radar targets cross and become unresolved; this is a concern, but with a reasonable track depth and an appropriate merged-measurement model the concern is considerably mitigated. Sonar targets, however, can become merged (in the same beam) for considerably longer, particularly with bearing-only measurements. In such cases the crossing times can be 100 scans long, and no reasonable depth exists for an multi-frame tracker that can "see" both ends of the merged period. Further, there is a demonstrable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…Equations (2)(3)(4)(5) provide predicted bounds on target position and velocity at time t. Assume that a measurement is available at time t, based on the following linear measurement model:…”
Section: A Strict Upper Bound Solution Maxmentioning
confidence: 99%
See 1 more Smart Citation
“…Equations (2)(3)(4)(5) provide predicted bounds on target position and velocity at time t. Assume that a measurement is available at time t, based on the following linear measurement model:…”
Section: A Strict Upper Bound Solution Maxmentioning
confidence: 99%
“…Recently, it has been observed that an opposite effect exists with trackers that utilize hard data association [3], which we denote as the track repulsion effect; this effect leads to track swapping in difficult target-swapping scenarios. In [4], multi-hypothesis tracking (MHT) technology is applied to the crossing-target problem.…”
Section: Introductionmentioning
confidence: 98%
“…We denote by n Z k1 the smaller measurement from the n th sensor at time k t , and the larger by n Z k1 . Equations (11)(12)14) still apply. Equations (8)(9)(10)13) are replaced by the following.…”
Section: Multi-target Filtering: the Ecmhtmentioning
confidence: 97%
“…It has been shown that the PDAF exhibits track coalescence [12][13], while the GNNF and MHT exhibit track repulsion [14][15][16]. Several approaches have been investigated to mitigate the impact of track coalescence in soft data association filters, see e.g.…”
Section: Multi-target Filtering: Two Classical Approachesmentioning
confidence: 99%
“…During the crossing, if the contacts are not of approximately equal signal-to-noise ratio (SNR), detections will be assigned to the higher SNR contact, and the lower SNR track will be lost. For contacts that have equal probability of detection (P D ), Willett et al [1] have recently shown that the estimated tracks generated with a standard assignment model exhibit a repulsion behavior during the crossing that violates the expected behavior of these large contacts, i.e., that they are known to travel at constant course and speed and cannot make sudden changes because of their size. This repulsion behavior causes problems downstream for algorithms that require state estimates to be consistent with contact trajectory.…”
Section: A Backgroundmentioning
confidence: 99%